Ecuador poverty report. (Washington, D.C. World Bank, 1996)
"Valuable report based on the Ecuador Living Standard Measurement Survey (1994). Uses total consumption expenditures. Provides a baseline reference for future work. Contrast with INEC's basic needs survey (item #bi 97002637#)"--Handbook of Latin Ameri can Studies, v. 57.
Includes bibliographical references.
Keywords: Poverty -- Government policy -- Ecuador; Poverty -- Ecuador